Prehistory - "Entwistle, Theodore Rowland" (Belitha Press London, 1991)
The book Prehistory by Theodore Rowland-Entwistle, part of the "My First Reference Library" series. Published in 1990 by Chrysalis Books, this 64-page volume serves as an introductory guide to prehistoric times for young readers. It features engaging "facts and feats" and "did you know?" sections that highlight intriguing details about prehistory. The book is designed to make learning about early human history accessible and enjoyable for children.